BASIC NOTIONS OF LINGUOCULTURAL ANALYSIS - Flyuza Gabdullinovna Fatkullina (Russian Language Studies, 2017)
The article represents the attempt to consider and comprehend methodological and conceptual notions, the definition and selection of which faces every researcher in the process of linguistic and cultural analysis of a text. It focuses on such key concepts as language, culture, language personality, linguistic worldview, cultural specificity, cultural code, concept, conceptual sphere, mythologem, etc. Despite numerous studies devoted to these realia, some aspects still require clarification and additional theoretical reasoning. The aim of the research in the article is also the study of sociocultural and linguistic trends of the formation of the national linguistic identity in the framework of intercultural communication and the characteristic of the features of the linguistic worldview of an individual.Based on the results of the study there is a conclusion that cultural linguistics is a scientific paradigm with a developed conceptual basis and definite categorical notion.